Implementation of 7 Good Habits of Great Indonesian Children Through Writing for Goals Journaling Habits activity - Christin, Maylanny; Hasanah, Ratih; Husnita, Husnita (Jurnal Abdimas, 2025)
The Great Indonesian Children's Habits Movement is a real manifestation of the Ministry of Education and Culture's commitment to developing a national education system that is oriented towards strengthening the nation's character. Through this movement, it will produce Indonesian children who are tough, superior and responsible both to themselves and to society, and will have an extraordinary impact on national change. This study aims to examine how community service activities are implemented, understand the perceptions and responses of junior high school students towards journaling activities as a medium for character building, and evaluate the effectiveness of journaling activities in implementing 7 good habits of great Indonesian children through writing for goals journaling habits activities. The habits that must be carried out by students every day are called the 7 habits of great Indonesian children, namely waking up early, praying, exercising, eating healthy and nutritious food, loving to learn, being in society, and going to bed early. This study uses a descriptive qualitative approach with the method used being the counseling and mentoring method in the form of workshop activities carried out in collaboration with SMP Sumatera 40 Bandung. The results of the study indicate that the implementation of 7 good habits of great Indonesian children in the lives of junior high school students greatly helps them to achieve their goals and build strong characters, which are an important part of the Great Indonesian Children movement. This activity not only increases self-awareness and goal-setting skills, but also strengthens children's characters through daily reflection. Journaling provides space for personal and meaningful learning. Therefore, the integration of positive habits in the world of education is an important step in realizing a competitive Indonesian golden generation that contributes to society. One effective way to instill positive habits is through writing for goals or journaling. Journaling can play a role in developing good habits and achieving goals gradually.